Horse transport - Marlin, David (MTT, 2008)
Transport of horses by road is extremely common and even air transport, though nowhere near as common, is considered routine. However transport is an unusual experience for horses and presents them with many potential stressors, including separation, noise, movement, space restriction, reduced air quality, reduced access to feed and water and an elevated head position. By far the majority of published information on transport relates to the sport or racehorse and in many cases to populations of animals acclimatised to transport. Much less has been published relating to the transport of horses for slaughter. Under these circumstances the animals being transported may be old and or ill or injured. They are usually transported with less concern that animals with a higher economic value and the level of stressors to which they are exposed may be higher resulting in failure to eat and drink sufficiently during transport. Other animals bred specifically for human consumption may have limited or no prior experience of transport. Transport has the potential to adversely affect almost all body systems, but it is the musculoskeletal, GI and respiratory tracts that are most commonly affected. An understanding of the effects of transport on the horse can permit the adoption of management practices that can improve the health and welfare of horse during transport.
Keywords: Ko; horse; transport; road; air